Evaluation of the strategic use of information technology in the rural banking sector in Ghana (a case study of Nwabiagya Rural Bank) - Aziale, Lawrence Kwami (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Philosophy in Business Information Technology, 2008